Duodenal Neuroendocrine Tumors: Location Matters!. Issue 5 (May 2016) - Sheikh, Mohd Raashid; Osman, Houssam; Cheek, Susannah; Hunter, Shanee; Jeyarajah, Dhiresh Rohan
Duodenal neuroendocrine tumors (NETs) are rare. Historically, when feasible a less aggressive surgical approach is considered. The aim of this study was to identify factors associated with prognosis and the necessity for more aggressive surgical procedures. All patients who underwent surgery for duodenal NETs between September 2005 and June 2014 were identified retrospectively. Data collected included clinical presentation, operative findings, and histopathological data. Eighteen patients underwent surgical management for duodenal NETs. Two patients underwent transduodenal excision (11%), two patients had partial duodenal resection (11%), two patients had antrectomy including 1st part of duodenum (D1) resection (33%), and eight underwent pancreaticoduodenectomy [PD (44%)]. On analysis, 2nd part of duodenum (D2) location was the most common site of duodenal NETs (n = 9, 50%). The odds of having a PD were 10 times higher when the lesion was in D2 location. The odds of having a positive lymph node are nine times higher when the lesion is in D2 region. The odds of having a positive lymph node are three times higher when lesion is greater than T1. D2 location of NETs is associated with higher odds of lymph node positivity and need for more extensive procedures like PD.